RELATIONSHIP BETWEEN RPOB MUTATIONS AND MINIMUM INHIBITORY CONCENTRATIONS OF RIFAMPICIN IN MULTI DRUG RESISTANT STRAINS OF MYCOBACTERIUM TUBERCULOSIS - Vaidya, Shashikant; Maniar, Jinesh; Muley, Shreyasi; Koppikar, Geeta; Kulkarni, Mohan; Chowdhary, Abhay (LIFE: International Journal of Health and Life-Sciences, 2015)
Tuberculosis is an infectious disease caused by obligate intracellular bacteria Mycobacterium tuberculosis, which has created a health problem worldwide. Incidence of Multi-drug resistance tuberculosis creates the scenario dangerous, which is resistant to both the first line drugs namely Rifampicin and ionized. Mutation in rpoB and inhA confers resistance to rifampicin and ionized respectively. In the present study we studied the relationship between rpoB mutations and minimum inhibitory concentrations of Rifampicin in Multi drug resistant(MDR) strains of Mycobacterium tuberculosis. Total 20 MDR strains were selected for the study. The mutations in the rpoB gene were identified by sequencing the PCR products. The minimum inhibitory concentrations of Rifampicin, was determined by Absolute Concentration method. Mutations conferring resistance to Rifampicin in Mycobacterium tuberculosis occurs in the defined region of 81 base pair of rpoB gene. The most frequent mutation found in Rifampicin resistant strain is at position 532, 526 and 516. Mutation occurring at this position results in high level of Rifampicin resistance. Mutation at 511, 518 and 522 is associated with low level of Rifampicin resistance.